Bisphenol A and S impaired ovine granulosa cell steroidogenesis. Issue 5 (May 2020) - Téteau, Ophélie; Jaubert, Manon; Desmarchais, Alice; Papillier, Pascal; Binet, Aurélien; Maillard, Virginie; Elis, Sébastien
Abstract : Bisphenols, plasticisers used in food containers, can transfer to food. Bisphenol A (BPA) has been described as an endocrine disruptor and consequently banned from the food industry in several countries. It was replaced by a structural analogue, Bisphenol S (BPS). BPA action on the steroidogenesis is one of the mechanisms underlying its adverse effects on the efficiency of female reproduction. This study aimed to determine whether BPS is a safe alternative to BPA regarding GC functions. Antral follicles (2–6 mm), of approximatively 1000 adult ewe ovaries, were aspired and GC purified. For 48 h, ovine GC were treated with BPA or BPS (from 1 nM to 200 µM) and the effects on cell viability, proliferation, steroid production, steroidogenic enzyme expression and signalling pathways were investigated. Dosages at and greater than 100 μM BPA and 10 µM BPS decreased progesterone secretion by 39% ( P < 0.001) and 22% ( P = 0.040), respectively. BPA and BPS 10 μM and previously mentioned concentrations increased oestradiol secretion two-fold ( P < 0.001 and P = 0.082, respectively). Only 100 µM BPA induced a decrease ( P < 0.001) in gene expression of the enzymes of steroidogenesis involved in the production of progesterone. BPA reduced MAPK3/1 phosphorylation and ESR1 and ESR2 gene expression, effects that were not observed with BPS. BPA and BPS altered steroidogenesis of ovine GC. Thus, BPS does not appear to be a safe alternative for BPA. Further investigations are required to elucidate BPA and BPS mechanisms of action.